Efeitos neurofisiológicos do isolamento social: do processamento olfativo ao comportamento emocional e cognitivo - Leonardo de Oliveira Guarnieri (2017)
Essential for survival, social interaction comprises a set of behaviors that enables, among other things, the maintenance of the emotional state of the animals and the duration of the social recognition memory (SRM). In fact, Swiss adult mice exposed to seven days of social isolation (SI) have their SRM limited to a few hours long. Interestingly, if the animal is maintained in SI in the presence of an enriched environment (EE) the SRM deficit is not expressed. In Chapter 1 of the present study, we investigated whether the SI condition also affects the emotional state of the animals. Biological indicators of depressive disorders, such as dopamine, noradrenaline and serotonin levels, and the olfactory bulb (OB) volume were compromised by SI. Using different paradigms, we found that SI induces type-depressive, anxious, and compulsive behaviors. The pharmacological treatments of diazepam (1mg / kg), fluoxetine (30 mg / kg) and desipramine (30 mg / kg) i.p.) were able to reverse or avoid the behavioral deficits caused by SI. Interestingly, the EE, in addition to its known promnestic effect, had antidepressant and anxiolytic effect in isolated animals. In Chapter 2, we tested the hypothesis that SI impairs social memory because it compromises the emotional state of animals. For this, we evaluated the effect of antidepressant drugs on SRM. Chronic treatment with fluoxetine, but not with antidepressants, was able to recover the SRM deficit. These results suggest that the transient change in the emotional state of isolated animals is not enough to rescue SRM. In previous studies, we have demonstrated that the effect of EE on recovering SRM from isolated animals depends on neurogenesis. One of the proposed mechanisms for the chronic action of fluoxetine is neurogenesis. We then evaluated the effect of chronic treatment with fluoxetine on neurogenesis levels. The analysis of cell proliferation, neurogenesis and astrogenesis showed that social isolation causes a decrease in cell proliferation and neurogenesis in the GR granular region and in the ventral hippocampus (VH) dentate gyrus. Chronic antidepressant treatments reversed this condition, but only fluoxetine was able to increase neurogenesis in the GR granular region. So far, our results suggest that there is no cause-and-effect relationship between type-depressive behavior and SRM deficit caused by SI. The Brain Derived Neurotrophic Factor (BDNF) is an important mediator of the plastic processes that occurred during the formation of long-term hippocampal-dependent memories. In addition, neurogenesis may exert its effects via production of BDNF. We then investigated the effect of IS on BDNF expression, but did not detect changes in basal levels. As BDNF is synthesized and released on demand, we administer recombinant BDNF (hrBDNF) in the hippocampus of isolated animals and observe a recovery of SRM. In contrast, the BDNF blocker (BDNFab) impaired SRM from pooled animals. Our results show that SI, besides decreasing neurogenesis in HV, compromises the production of BDNF dependent on learning in the dorsal hippocampus, which impairs SRM. We can then speculate that EE and chronic treatment with fluoxetine, by restoring both neurogenesis and BDNF production, recover SRM in isolated animals. The main effect of fluoxetine is to increase the availability of serotonin. To test whether serotonin levels in OB are indeed essential for the formation of SRM, we inhibit the main neural pathway that feeds OB with serotonin. Using the DREADDs (Designer Receptors Exclusively Activated by Designer Drug) we inhibited the serotonergic projections from the dorsal nucleus of the raphe in OB prior to acquisition or recall of the SRM. Our results showed that this pathway is necessary for the formation and evocation of SRM. The main sensory input to SRM is smell. In addition, deprivation of olfactory function in rodents induces type-depressive behavior. In Chapter 3 we investigated the impact of SI on different behavioral paradigms dependent on smell. We observed that isolated animals are able to detect social, non- social and aversive odors. However, they are unable to discriminate familiar social odors from new ones in the same context. In addition, we also verified the effect of serotoninergic modulation on OB on olfactory function. We observed that the inhibition of the serotonergic projections of the raphe nucleus to OB hinders the discrimination of odors. Together, our results show that SI changes the neurochemistry and morphology of the olfactory bulb and hippocampus, as well as compromising emotional behavior and social memory. However, SI preserves the olfactory function. Although our results suggest that there is no cause-and-effect relationship between depressive behavior and SRM deficiency in isolated animals, pharmacological treatment.